Development of two high-yielding, consumer-acceptable apple banana hybrids (Musa species, AAB genome group) with resistance to Fusarium oxysporum f. sp. cubense race 1 - Buregyeya, H.; Tumuhimbise, Robooni; Kubiriba, Jerome; Talengera, D.; Nowankunda, K.; Arinaitwe, G.; Tushemereirwe, Wilberforce K.; Karamura, D.; Karamura, E.B.; Rubaihayo, P. (Academic Journals, 2018)
Fusarium wilt of bananas (Musa species) is caused by Fusarium oxysporum f. sp. cubense (Foc). Foc race 1 in particular affects dessert bananas in Uganda, causing >60% yield loss. This study was conducted to assess the performance of two new apple banana genotypes for bunch yield, resistance to Foc race 1 and consumer acceptability. The new apple banana genotypes (NAMU1 and NAMU2), along with two check cultivars, one susceptible but preferred by consumers (Sukali ndiizi) and the other resistant (Yangambi-KM5), were evaluated at the National Agricultural Research Laboratories in Uganda. Bunch yields of the two new apple bananas were higher than those of check cultivars by >50%. NAMU1 and Yangambi-KM5 showed no symptoms of Foc race 1, whereas NAMU2 showed mild symptoms on its corms. Sukali ndiizi showed severe pseudostem splitting and corm discoloration as the key symptoms of Foc race 1. The consumer acceptability of NAMU1 and NAMU2 was as high as that of Sukali ndiizi, implying that they can be perfect substitutes for the Foc race 1 susceptible Sukali ndiizi.